Answer:
Step-by-step explanation:
x-y=7
-3x+9y=-39
Divide the second equation by 3
-x +3y = -13
Add this to the first equation
x-y=7
-x +3y = -13
----------------------
0x +2y = -6
Divide by 2
2y/2 = -6/2
y = -3
Now find x
x-y = 7
x -(-3) = 7
x+3 = 7
Subtract 3 from each side
x = 4
(4,-3)
Or by substitution
x-y=7
solve for x
x = 7+y
-3x+9y=-39
Substitute y+7 in for x
-3(7+y) +9y = -39
Distribute
-21 -3y +9y = -39
Combine like terms
-21 +6y = -39
Add 21 to each side
6y = -18
Step-by-step explanation:
|5| - |-3| is 2
Answer:
Directions - Identify the key components, create an exponential equation, then answer the questions.
Exponential Form: y=a\cdot b^{x},\ a\ is\ the\ \textit{starting}\ \textit{value},\ b\ is\ the\ base\ (rate).\y=a⋅b
x
, a is the starting value, b is the base (rate).
In a small town, the stray dog population is rapidly increasing. there are currently 15 stray dogs, and it is estimated that the population will triple every year. How many dogs will there be after 1 year? 2 years? 3 years?
1) a = 15
4) Dogs after 1 years = 45
2) b = 3
5) Dogs after 2 years = 135
3) Equation:
y= 15 ×3x
6) Dogs after 3 years =
405
Step-by-step explanation:
It should be 555^3=170953875
Oh easy the answer to that question is 4